(untitled) (Bangladesh Journal of Zoology, 2021)
Pest management relies on proper identification of insect species, which usually depends on morphological keys. In this research, DNA barcoding was used to identify three pest species of genus Aulacophora (A. foveicollis, A. lewisii and A. indica) attacking horticultural crops in Bangladesh. Accurate phylogenetic information and evolutionary divergence data were supported and evidenced by various parameters, including the rates of substitution, nucleotide composition and genetic divergence. The nucleotide composition of these three species indicates that the total adenine and thiamine content (A+T, 67.3%) was higher than the guanine and cytosine content (G+C, 32.87%). Intraspecific genetic divergence ranged from 0.0158-0.1415. To confirm the origin and evolution, phylogenetic tree and haplotype network was drawn. Both the maximum likelihood and neighbor joining analyses showed that A. indica and A. foveicollis were clustered in one group, and A. lewisii was originated from another group. Haplotype showed that A. lewisii has the highest amount of mutational steps among the sequenced pests and genetically distant species from its common ancestors by 78 mutational numbers. Present investigation can be reliably treated for developing reference libraries for species identification via sequence matches and designing specific pest management approach. Bangladesh J. Zool. 48(2): 399-411, 2020